Experimental Study on the Natural Deposition Characteristics of Erosols in Containment - Tian, Lin Tao; Gu, Haifeng; Yu, Huiyu; Chen, Junyan (Frontiers in Energy Research, 2020)
Abstract: Against the background of natural deposition of aerosols in containment under severe accident conditions, the relevant experimental facility was designed and constructed to study the decay constant of natural deposition of aerosol. The TiO2 was used as the aerosol medium, and the decay constant of aerosol was studied. The results show that when the aerosol concentration is <15000/cm3, the decay constant of aerosol increases with the increase of the particle size. However, when it is ≥15000/cm3, because the polymerization of small particles into large particles accelerate the deposition of particles with smaller size, the decay constant of aerosol decreases first and then increases with the increase of the particle size. In addition, the effect of electrostatic on the decay constant of natural deposition of aerosol was studied. When the electrostatic effect is present, the decay constant of aerosol increases significantly. Finally, the natural deposition characteristics of aerosols were obtained.